The Effect Of Transformational Leadership On Organizational Citizenship Behavior (Ocb) Mediated By Quality Of Work Life (Qwl) And Organizational Commitment In The Chemical Manufacturing Industry Sector In Cilegon City - Dwiputri, Nadia Mutiara; Yusuf, Furtasan Ali; Nuryanto, Uli Wildan (Amkop Management Accounting Review (AMAR), 2025)
The background of this study is the crucial role of transformational leadership in fostering OCB in the chemical manufacturing industry, which faces significant challenges related to safety and quality of work. QWL and organizational commitment are considered mediating factors that can strengthen the influence of leadership on OCB in this work environment. The purpose of this research is to analyze the effect of transformational leadership on employee OCB in the chemical manufacturing sector of Cilegon City, simultaneously assessing the mediating roles of QWL and organizational commitment. The research method employed is quantitative using Structural Equation Modeling based on Partial Least Squares (PLS-SEM). Data were collected via questionnaires distributed to 300 permanent employees across five chemical manufacturing companies in Cilegon City. Path analysis was conducted to test the direct and indirect relationships among variables. The results indicate that transformational leadership significantly affects OCB both directly and indirectly through the mediation of QWL and organizational commitment. Moreover, QWL significantly influences organizational commitment and OCB. These variables collectively explain 87.2% of the variance in employee OCB. The conclusion highlights the importance of developing transformational leadership and enhancing QWL and organizational commitment to improve OCB in the chemical manufacturing industry. Practical implications suggest the need for integrated programs combining leadership development, QWL, and organizational commitment to foster sustainable organizational performance.